Diagnostic test accuracy of ultrasound for synovitis in rheumatoid arthritis: systematic review and meta-analysis. (3rd March 2017) - Takase-Minegishi, Kaoru; Horita, Nobuyuki; Kobayashi, Kouji; Yoshimi, Ryusuke; Kirino, Yohei; Ohno, Shigeru; Kaneko, Takeshi; Nakajima, Hideaki; Wakefield, Richard J; Emery, Paul
Abstract: Objective: To evaluate diagnostic test accuracy of US compared with MRI for the detection of synovitis in RA patients. Methods: A systematic literature search was performed in the PubMed, EMBASE, Cochrane Library and Web of Science Core Collection databases. Studies evaluating the diagnostic test accuracy of US for synovitis detected by MRI as the reference standard for wrist, MCP, PIP and knee joints were included. To assess the overall accuracy, we calculated the diagnostic odds ratio using a DerSimonian–Laird random effects model and the area under the curve (AUC) for the hierarchical summary receiver operating characteristics using Holling's proportional hazards models. The summary estimate of the sensitivity and specificity were obtained using the bivariate model. Results: Fourteen of 601 identified articles were included in the review. The diagnostic odds ratio was 11.6 (95% CI 5.6, 24; I 2 = 0%), 28 (95% CI 12, 66; I 2 = 11%), 23 (95% CI 6.5, 84; I 2 = 19%) and 5.3 (95% CI 0.60, 48; I 2 = 0%) and the AUC was 0.81, 0.91, 0.91 and 0.61 for wrist, MCP, PIP and knee joints, respectively. The summary estimates of sensitivity and specificity were 0.73 (95% CI 0.51, 0.87)/0.78 (95% CI 0.46, 0.94), 0.64 (95% CI 0.43, 0.81)/0.93 (95% CI 0.88, 0.97), 0.71 (95% CI 0.33, 0.93)/0.94 (95% CI 0.89, 0.97) and 0.91 (95% CI 0.56, 0.99)/0.60 (95% CI 0.20, 0.90) for wrist, MCP, PIP and knee joints, respectively. Conclusion: US is a valid and reproducible technique for detecting synovitis in the wrist and finger joints. It may be considered for routine use as part of the standard diagnostic tools in RA.